2015
DOI: 10.1109/tps.2015.2424154
|View full text |Cite
|
Sign up to set email alerts
|

High Power Lateral Silicon Carbide Photoconductive Semiconductor Switches and Investigation of Degradation Mechanisms

Abstract: Several generations of high power, lateral, linear mode, intrinsically triggered 4H-SiC photoconductive semiconductor switch designs and their performance are presented. These switches were fabricated from high purity semi-insulating 4H-SiC samples measuring 12.7 mm × 12.7 mm × 0.36 mm and were able to block dc electric fields up to 370 kV/cm with leakage currents less than 10 μA without failure. Switching voltages and currents up to 26 kV and 450 A were achieved with these devices and ON-state resistances of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…They are, among others, SI GaP, SI 6H-SiC, SI 4H-SiC and SI GaN with a band gap width of 2.26, 3.0, 3.23 and 3.39 eV respectively at 300 K [6,8]. Research confirms better properties of PCSS made of SI 6H-SiC, SI 4H-SiC and SI GaN compared to switches made of SI GaAs [8,9]. PCSS switches can work in linear (conventional) and non-linear (avalanche) modes.…”
Section: Introductionmentioning
confidence: 63%
“…They are, among others, SI GaP, SI 6H-SiC, SI 4H-SiC and SI GaN with a band gap width of 2.26, 3.0, 3.23 and 3.39 eV respectively at 300 K [6,8]. Research confirms better properties of PCSS made of SI 6H-SiC, SI 4H-SiC and SI GaN compared to switches made of SI GaAs [8,9]. PCSS switches can work in linear (conventional) and non-linear (avalanche) modes.…”
Section: Introductionmentioning
confidence: 63%
“…Another work showed that SiC PCSS could block DC electric fields up to 705 kV/cm with leakage current < 0.1 mA, and switch voltages up to 30 kV into a 30 load [17]. DC blocking fields of 370 kV/cm with leakage currents less than 10 μA and switching currents of 450 A have been reported in 4H-SiC samples measuring 12.7 mm × 12.7 mm × 0.36 mm [19].…”
Section: Introductionmentioning
confidence: 98%
“…Other mentioned SI materials have wider band gaps and, theoretically, should be able to block higher voltages and conduct higher current values than switches made of SI GaAs. Recent studies have experimentally shown that performance of PCSSs made of SI GaP, SI 6H-SiC, SI 4H-SiC, and SI GaN is much better compared to that made of SI GaAs [3,12,13].…”
Section: Introductionmentioning
confidence: 99%